Ultrasound Parameters of Thyroid Nodules and the Risk of Malignancy: A Retrospective Analysis - Wang, Minxin (Cancer Control, 2020)
Ultrasonography-guided fine-needle aspiration biopsy is the common choice for diagnosis of the suspected thyroid nodule. An algorithm(s) that finds the malignant potential of a nodule preoperatively, to overcome unnecessary diagnostic methods, does not exist. The objective of the study was to correlate thyroid nodule sizes measured by ultrasonography and risk of malignancy assessed by cytologic and histologic examinations. Data regarding fine-needle aspiration cytology and the results of histologic examinations of surgical specimens of 260 nodules were collected and analyzed. The macro or multiple calcifications, the complex echo pattern, and posterior region homogeneity were considered suspicious in ultrasonography. Bethesda system for classification of thyroid nodules was used for cytopathology. Histopathology performed as per the 2004 World Health Organization classification system. The benefit score analysis was performed for determination of clinical usefulness. Twenty-eight of 49 malignant nodules and 46 of 68 malignant nodules detected through ultrasound following fine-needle aspiration cytopathology and histopathology were <2 cm in size. A correlation was found for malignancy rate detected by ultrasonography-guided fine-needle aspiration cytology and those of the surgical specimen (r = 0.945, P = .015, R (2) = 0.894). Ultrasonography-guided fine-needle aspiration cytology had 0.994 sensitivities, 0.721 accuracies, and 0.08 to 0.945 diagnostic confidence for the detection of malignant nodules. Nodule size less than 2 mm (P = .011) was associated with the malignancy potential of thyroid nodules. Ultrasonography-guided fine-needle aspiration cytology had 19 (7%) results as a false negative and 1 (1%) results were false positive. Ultrasound-guided fine-needle aspiration cytopathology reported oversize of thyroid nodule than original but can predict the risk of malignancy. Level of Evidence: III.